National industrial investment fund and China's integrated circuit industry technology innovation - Xin Tong; Xiaomeng Wan (Journal of Innovation & Knowledge (JIK), 2023)
Since the emergence of information technology, the integrated circuit industry has been a major contributor to sustained economic expansion. This paper proposes a theoretical model premised on the pertinent theories of technological progress in late-mover countries and concludes that it is challenging for late-mover countries to rely solely on market mechanisms to elevate the level of social technology; state policy support is indispensable. In addition, this paper employs the panel data of 81 A-share listed integrated circuit companies in China from 2011 to 2019 and implements the Difference in differences (DID) method to evaluate the impact of the National Integrated Circuit Industry Investment Fund on the technological innovation of the integrated circuit industry, and adopts the double-difference propensity score matching method for supplemental verification. This paper concludes that the National Integrated Circuit Industry Investment Fund has significantly enhanced industrial technological innovation and that the estimated results premised on the difference-in-difference based on propensity score matching (PSM-DID) method and the placebo test are not substantially differentiated from the benchmark regression results. The effects of industrial investment funds on policy are evidently different across different regions and industry chains, in accordance with research on industry heterogeneity. The promotion effect of the core link is significantly stronger than the support link in terms of branches of the industrial chain, and the Pearl River Delta region has a more pronounced promotion effect in terms of regions. Verification of the mechanism demonstrates that industrial investment funds can relieve corporate financing constraints, optimize corporate human capital structure, promote corporate RandD (research and development) investment, and subsequently promote technological innovation in the integrated circuit industry through the aforementioned three effects. On the one hand, the research presented in this paper offers empirical support and policy guidance for the implementation of technological innovation in China's integrated circuit industry. On the other hand, it also has significant reference value for fostering the growth of industrial investment funds.
Keywords: 650; Firm heterogeneity; Innovation path; Mechanism; National Integrated Circuit Industry Investment Fund; Technology innovation